Implementation of Dual Expertise Policies for Vocational High School Teachers in Demak Regency (Journal of Vocational and Career Education, 2018)
Vocational education policies that are currently being implemented to produce skilled workers in their fields, one of them are, the proportion of Senior High School students: Vocational High School students are 30%: 70%, changes in the number of comparisons have an impact on the needs of the number of teachers, while temporary vocational teachers (productive teachers) in other expertise/specialization programs or other subjects, the number of teachers exceeds the amount that is required. The dual expertise program is a program to provide additional teaching authority for Vocational High School/Senior High School teachers who teach certain subjects to become productive subject teachers in Vocational High Schools in certain skill competencies that are different from previous skills competencies and relevant to their educational background. The objective of this study is to review and describe the implementation of dual expertise policies for Vocational High School teachers and their impact on Demak Regency. The process of preparation, implementation, and results of activities is described so that they can be understood as aspects related to the issues regarding the policy. This research was qualitative research. To get the validity of the data, the researchers used several data validity checking techniques, they were: (1) Technique of checking credibility; (2) Technique of transferability; (3) dependency checking technique. The data analysis used in this study was qualitative descriptive analysis. The result of this study is the impact of implementing dual expertise activities has not been significant towards the fulfillment ofÂ  the needs of productive teachers. It is known that the problem is the element of communication, namely the lack of delivery of information from policy actors to the teacher. For other elements such as disposition, resources, and bureaucratic structure, it has been implemented well.